Therapeutic use of biologically produced sulfur nanoparticles from Allium fistulosum against antibiotic-resistant foodborne pathogens - AISHA SADDIQUA; SHAKEEB ULLAH; MUHAMMAD SHUAIB KHAN; SAIFUR REHMAN; ADAMU ABDUL ABUBAKAR; KAMRAN SAFDAR; SUMERA ALI; SADAF JAVARIA; ARZO KANWAL; SYEDA NAYAB BATOOL; FARHEEN BHATTI; TEGUH HARI SUCIPTO; ARIF NUR MUHAMMAD ANSORI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Saddiqua A, Ullah S, Khan MS, Rehman S, Abubakar AA, Safdar K, Ali S, Javaria S, Kanwal A, Batool SN, Bhatti F, Sucipto TH, Ansori ANM. 2024. Therapeutic use of biologically produced sulfur nanoparticles from Allium fistulosum against antibiotic-resistant foodborne pathogens. Biodiversitas 25: 2348-2354. Food spoilage is a significant issue since foodborne illnesses affect millionsworldwide. The main root cause of food spoilage is the presence of microbes, some of which show resistance to commercially available antibiotic drugs. Therefore, it is essential to search for fresh and effective antibacterial medications. Nanotechnology can give solutions to fight against foodborne pathogens. Sulfur nanoparticles show many beneficial and effective results as antimicrobial agents. The aim of this study was to evaluate the efficacy of biologically synthesized sulfur nanoparticles from Allium fistulosum to inhibit antibiotic-resistant foodborne pathogens. The green synthesis of sulfur nanoparticles was done by combining plant leaf extract with sodium sulfide. This study used the plant Allium fistulosum to make sulfur nanoparticles. The characterization of SNPs was done through a scanning electron microscope, UV spectrophotometer, fourier transform infrared spectrometer, and nanoparticle tracking analysis. Then, the antimicrobial properties of the bioengineered sulfur-based nanoparticles against foodborne pathogens were checked alone and in combination with market-available antibacterial agents. Aspergillus flavus and Salmonella typhi were among the foodborne pathogens against which SNPs' in-vitro antibacterial activity was tested. Sulfur nanoparticles from Allium fistulosum had 291 nm absorption spectra showing to be almost 100 nm in size and had a spherical shape. The strongest antibacterial efficacy against S. typhi was observed by SNPs (24 mm). Synergistic antibacterial action was seen when nanoparticles were combined with antibiotics of commercial importance. A noticeable antifungal effect against A. flavus was observed by combining SNPs with amphotericin B. The findings of in vitro studies prove that novely designed sulfur nanoparticle have profound impacts on microorganisms. It was also observed that the effect of antibiotics like ampicillin and amphotericin B was enhanced when coupled with nanoparticles.